Microbiological quality of home production of sprouts in Brazil - SALGADO, Vanessa dos Santos Chiappetta Nogueira; BRITO, Flávia Oliveira; RODRIGUES, Paula Stephany de Melo; ANTUNES, Adriane Elisabete Costa; GOUVÊA, Raquel; ZAGO, Lilia; MIYAHIRA, Roberta Fontanive (Food Science and Technology, 2025)
Sprouts are considered foods with high nutritional value, tasty, and easy to produce even in domestic environments. However, their consumption has been linked to various food outbreaks, as they are susceptible to microbial contamination. This work aimed to evaluate the microbiological quality of lentil, wheat, and chia sprouts germinated in a domestic environment and the effectiveness of the sprout and seed sanitization process. Total coliforms, Escherichia coli, mesophilic aerobes, and Bacillus cereus were determined, and the presence of Salmonella spp. and Listeria monocytogenes was investigated. No strains of Salmonella spp., E. coli, and L. monocytogenes were found. However, a high microbial load of total coliforms was found in the sprouts. B. cereus was found only in the wheat and chia sprout samples. The sanitization process with sodium hypochlorite was able to reduce the microbial load of the sprouts, but the load remained high. Seeds should be marketed only when they are suitable for home germination after going through a more efficient decontamination process. In addition, competent authorities are supposed to create and widely disseminate a document of good production practices for safer domestic cultivation of sprouts.